The challenges of occupational safety and health acts requirement at construction site from the perspective of safety officer - Nurul Fieqah, Ahmad Kazimi (2016)
Implementation of Occupational Safety and Health Act (OSHA) in the construction sector is not a new thing. Occupational Safety and Health Act (OSHA) in Malaysia is the Act which provides the legislative framework to secure the safety, health and welfare among all Malaysian workforces and to protect others against risks to safety or health in connection with the activities of persons at work gazetted on 24th February 1994 by Malaysian Parliament. OSHA has issued Guidelines for Managing the voluntary protection program to encourage employers to do more than just comply with regulations to prevent injuries and occupational diseases. However, this is often a problem when there are situation implications OSHA at the construction site. We often associate implications OSHA safety requirements is one of the main tasks of the office. Other than that, implementation of OSHA requirements at construction site involves many parties. Cooperation is among all parties very important in helping the effectiveness of the implementation of OSHA requirements. This is a challenging task for the safety officer. However the challenge comes from the OSHA requirements. Nevertheless, there are many aspects that affect the implications OSHA requirements as a challenging task. That aspect is only known by the safety officer itself.